PROLONGED DWINDLING CHARACTERISES THE ILLNESS TRAJECTORY OF NURSING HOME RESIDENTS AT THE END OF LIFE. Issue 1 (1st March 2014) - Finucane, AM; Stevenson, B; Murray, SA
Abstract : Introduction: Three illness trajectories have been identified: (i) a short period of evident decline typically experienced by patients with cancer; (ii) long term limitations with intermittent serious episodes typically experienced by patients with organ failure; and (iii) prolonged dwindling typically experienced by patients with frailty or dementia. An understanding of a patient's illness trajectory facilitates anticipatory care planning and decision-making as end-of-life approaches. Aim(s) and method(s): To determine the dominant illness trajectories of nursing care home residents. As a secondary aim we explored multimorbidity in this group. Data was collected by care home staff with support from community palliative care nurse specialists as part of a larger project to improve palliative care in South Edinburgh care homes. Results: Data concerning 77 residents was collected. The dominant illness trajectory of 90% of residents was characterised by prolonged dwindling. Further analysis revealed that 30% of residents experienced mixed illness trajectories. About half of those with mixed trajectories experienced dementia and cancer while half experienced dementia and organ failure. 67% of residents experienced two or more chronic morbidities. Overall, 78% of deceased residents had dementia. Conclusion(s): The vast majority of nursing home residents experienced prolonged dwindling prior to death. Most had multiple morbidities and high symptom burden. Interventions to improve palliative care in nursing homes need to be modelled on patients who experience prolonged dwindling characterised by dementia and multimorbidity.